PENGARUH PENGENDALIAN INTERN DAN LOCUS OF CONTROL TERHADAP KINERJA KARYAWAN - Setyaningsih, Ayu; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to find out the influence of internal control and locus of control to the employeeperformance. The population of this research is all employees of PT. Yasa Bali Sujati, the research samples ofthis research are employees and supervisors. The data collection technique has been by using primary has beencollected by issuing questionnaires. The data analysis method has been by using multiple linear regressionsanalysis. The result of this research shows that (1) internal control give influence to the employee performance,it means that the control activity within the company, policy and control procedures should be determined andimplemented to assist and to assure that activities which have been identified by the management to encounterthe risk to the achievement of entity goals has to be conducted effectively; (2) locus of control give influence tothe employee performance, it means that locus of control which has been managed properly by the individualwill be able to improve the individual performance which has been running well previously and it will be betterin the future, it is supported by the measurement of individual performance which is getting better and it alsogives influence to the performance assessment.Keywords: internal control, locus of control, employee performance.